Diversity and genetic population structure of the Brazilian sharpnose shark Rhizoprionodon lalandii - Mendonça, Fernando Fernandes; Oliveira, Claudio; Gadig, Otto Bismarck Fazzano; Foresti, Fausto (Wiley, 2013)
Similar to many small, range-restricted elasmobranchs, the Brazilian sharpnose shark (Rhizoprionodon lalandii) is listed as 'data deficient' by the International Union for the Conservation of Nature (IUCN). Data on stock assessment and sustainability are scarce, and there is no information on population structure. This constitutes a management problem because this shark comprises approximately 50% of the catch of small coastal sharks in Brazil. In this study, populations of R. lalandii distributed from the Caribbean to southern Brazil were investigated using sequences from the mitochondrial DNA control region. Analysis of molecular variance revealed strong structuring between population samples from the Caribbean and those from the Brazilian coast (F{cyrillic}ST=0.254, P<0.0001). Significant differences in the rates of genetic diversity between these major areas were also detected. The observed levels of population structuring are likely to be driven by female phylopatry. Therefore, the identification of both mating and nursery areas with parallel ban/restriction of fishing in these areas may be critical for the long-term sustainability of these populations. © 2013 John Wiley & Sons, Ltd.
Keywords: Conservation genetics; Fishery management; Marine phylogeography; Mitochondrial DNA; Shark